Analysis of an “international teaching practicum” as a program for achieving “teacher agency” and strengthening “technological pedagogical content knowledge” - Kim, Youn Ock; Yun, Soyoung; Sol, Yang Hwan (Frontiers in Education, 2023)
This research is to study the achievement of Korean pre-service teachers’ teacher agency through their experiences in an international teaching practicum (ITP). This study also diagnoses the domestic pre-orientation (DPO) program of G University to seek the possibilities of developing as a TPACK strengthening program. The participants of this study were five female Korean pre-service teachers who were in the ITP in 2015-2016. The data were collected in two different time slots; the teaching diaries and ITP reports from the Korean pre-service teachers, DPO teaching materials, and program instructor’s fieldnotes were collected in 2016, then the interview was conducted in 2018. To study their teacher agency achievement, the three chordal triads of agency; the iterational dimension, the practical-evaluative dimension, and the projective dimension were spotlighted and used as the lens to analyze the data. Also, the DPO program was analyzed based on the elements of TPACK competencies. The research represent that the ITP was a trigger experience for the Korean pre-service teachers, in terms of achievement of teacher agency. The participants could project their aspirations, then decided and executed what they had learned from the ITP to their actual Korean classrooms. Also, the need to reconstruct the DPO program to be able to assist the pre-service teachers’ TPACK achievement has been raised.